Supplier Performance Evaluation Model Using the Best-Worst Method and Analytic Network Process in Supplier Relationship Management - Yuniar Aulia Hanifah; Iwan Vanany (Journal of Social Research, 2026)
Supplier Relationship Management (SRM) is an essential component of modern supply chain management because it affects raw material availability, product quality, production continuity, and operational sustainability. The complexity of supplier evaluation requires a multi-criteria decision-making approach that accommodates interrelationships among influencing factors. This study aimed to identify supplier performance evaluation criteria, determine criterion priority weights using the Best-Worst Method (BWM), analyze interdependencies among criteria using the Analytic Network Process (ANP), and formulate an integrated BWM–ANP supplier performance evaluation model within the SRM framework at PT XYZ. This quantitative study employed surveys, observations, interviews, questionnaires, and documentation in PT XYZ’s Purchasing Department from July to October 2025. Primary data were obtained from procurement experts, while secondary data were derived from internal company documents. SRM indicators were identified through a literature review and expert judgment, with data processed using Super Decisions® software. The results produced an integrated supplier performance evaluation model comprising five main criteria: quality, price, delivery accuracy, lead time, and supplier risk. The final weights showed that quality was the most dominant criterion (0.5185), followed by delivery accuracy (0.2182), price (0.1241), lead time (0.1021), and supplier risk (0.0370). The model provides a basis for supplier evaluation and clustering, supporting more objective, structured, and comprehensive supplier management decisions. The study also contributes to the development of Multi-Criteria Decision Making (MCDM)-based supplier evaluation models and offers practical implications for strengthening SRM strategies at PT XYZ.